PERENCANAAN FONDASI POERPILECAP PADA REHABILITASI PEMBANGUNAN GEDUNG DISKOMINFO 3 LANTAI KOTA SERANG PROVINSI BANTEN - NILA Prasetyo Artiwi; Gunawan M Noor; Muhammad Sidik (Journal of Sustainable Civil Engineering (JOSCE), 2019)
The foundation is a construction at the base of the structure / building (substructure) which functions to carry the load from the upper structure to the subsoil below without causing soil shear failure and excessive land settlement / foundation. The construction of the Communication and Information Office Building is located on Jalan Jenderal Sudirman No.25, Serang City, Banten Province, the office uses the foundation of a poer pile cap. But in its implementation there are deviations so that it needs to be re-planned. The parameters calculated and planned are the dimensions of the pile cap, the pile cap and the carrying capacity of the foundation arising from the structural load on it and the quality of the concrete that should be used. The purpose of the re-planning research is to obtain a calculation analysis of differences pile cap structure before and after re-planned. The building has a length (P) of 16 m, building width (L) 12 m. After calculation using the ETABS v.16 program, the original design of the previous foundation thickness (hf) is 500 mm, concrete quality (fc ') 19.3 Mpa (K-225), foundation support strength (Pu) is unknown, and after review, foundation thickness (hf) to 600 mm, concrete quality (fc ') 26.4 Mpa (K-300), and foundation support strength (Pu) 4,207.50 KN.